Novel Epoxidation Reaction of Perfluoroalkenes with Triethylamine N-oxide - Cai, Xingwei; Sha, Min; Ming Pan, Ren (Asian Journal of Chemistry, 2012)
Triethylamine N-oxide was found to be nice reagent for the epoxidation of tri- and tetra-substituted perfluoroalkenes in good to excellent yields. By coupling this reaction with the N-oxidation of triethylamine by hydrogen peroxide, a novel catalytic epoxidation method was developed.